Komposisi Fisik Karkas Ayam Kampung Super Yang Diberi Tepung Gaplek Terfermentasi - Anastasia Pola; Ni Made Ayu Gemuh Rasa Astiti; I Gede Sutapa (GEMA AGRO, 2021)
Improving the quality of feed can be done by using additional feed that does not compete with human needs, has nutritional content, is easy to obtain and is cheap. Cassava flour is an alternative feed ingredient that can be used for native chickens. This study used a completely randomized design (CRD) with 5 treatments and 3 replications. each test using 5 chickens. of the five treatments were R0 = control ration without addition of fermented cassava flour, R1 = ration containing 10% fermented cassava flour, R2 = ration containing 20% ​​fermented cassava flour, R3 = ration containing 30% fermented cassava flour, R4 = ration containing 40 % fermented cassava flour. The parameters observed were the physical composition of the carcass of the chest and thighs which consisted of meat, bone and subcutaneous fat or skin. The data obtained were analyzed by means of variance. If there is a significant difference between treatments, it is done by using the Duncan test. The results showed that the weight of the meat, bones, skin of the breast and the weight of the thigh meat gave significantly different results (P <0.05), while the bones and skin of the thigh gave insignificant differences (P> 0.05)